VD_FINDINFO AVS 46/12 - 6/2014 vom 9. Januar 2014 - VD Tribunal cantonal (2014)
AVS, RENTE ORDINAIRE, LACUNE DE COTISATION, BASE DE CALCUL | 1a al. 1 LAVS, 29 al. 2 LAVS, 29bis LAVS, 29ter LAVS, 13 LPGA, 50 RAVS, 52 RAVS